Course Scheduler and Recommendation System for Students - Uslu, Suleyman; Ozturan, Can; Uslu, Mehmet Fatih (IEEE, 2016)
Every semester, university students need to decide their course programs, and as the number of course offerings increase, it becomes challenge to form a schedule for the semester courses to be taken. In addition, students might have difficulty in finding courses that can match their schedules and course preferences. In order to address these problems, we build Mecanin, an online platform for Bogazici University students that provides an optimum schedule and course recommendation tools. In this paper, we propose an integer programming model to optimize course programs and also a recommendation algorithm to suggest courses to students. Both algorithms are tested and compared, and the results are presented.
Keywords: integer programming; collaborative filtering; course recommendation; INTEGER; TIMETABLES; ALGORITHM; Computer Science